Formulation and Assessment of an Instant Degrading Film of the Poorly Soluble Medicament Cilnidipine - Pandey, Mayankesh; Purohit, Debashis; Patel, Shweta; Kumar, Ashish; Kumar, Neeraj; Gupta, Anubha (Journal for Research in Applied Sciences and Biotechnology, 2023)
Cilnidipine, also known as dihydropyridine, is a calcium antagonist that has that chemical formula. It does this by blocking L-type calcium channels, which prevents calcium from entering the capillaries. This results in a reduction in blood pressure. When taken orally in tablet form, the medicine has a lower bioavailability than when it is injected. This is because it is less water-soluble. A substance was produced as a result of the combination of PEG 400 and propylene glycol that was neither hard nor sticky in nature. Inclusion complexes that are produced with cyclodextrin contribute to an improvement in the drug's solubility and release. We studied the influence that PEG 400 and propylene glycol would have on the formula by using a factorial arrangement. A 32-full factorial design was utilised in order to attain the maximum level of optimization for the rapidly disintegrating film. In in vitro drug release investigations using PEG 400 and propylene glycol, independent parameters such as pH, thickness, weight uniformity, percent drug content, folding endurance, and disintegration time were examined and analysed.